Search for Higgs boson production in association with a high-energy photon via vector-boson fusion with decay into bottom quark pairs at √s=13 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Klassen, Martin; Krishnan, Anjali; et al. (Journal of high energy physics, 2021)
A search is presented for the production of the Standard Model Higgs boson in association with a high-energy photon. With a focus on the vector-boson fusion process and the dominant Higgs boson decay into b-quark pairs, the search benefits from a large reduction of multijet background compared to more inclusive searches. Results are reported from the analysis of 132 fb−1 of pp collision data at $$ \sqrt{s} $$= 13 TeV collected with the ATLAS detector at the LHC. The measured Higgs boson signal yield in this final-state signature is 1.3 ± 1.0 times the Standard Model prediction. The observed significance of the Higgs boson signal above the background is 1.3 standard deviations, compared to an expected significance of 1.0 standard deviations.